2021
DOI: 10.1002/2211-5463.13094
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical antagonism between human lysozyme and AMPs against Pseudomonas aeruginosa

Abstract: Combinations of human lysozyme (hLYS) and antimicrobial peptides (AMPs) are known to exhibit either additive or synergistic activity, and as a result, they have therapeutic potential for persistent and antibiotic‐resistant infections. We examined hLYS activity against Pseudomonas aeruginosa when combined with six different AMPs. In contrast to prior reports, we discovered that some therapeutically relevant AMPs manifest striking antagonistic interactions with hLYS across particular concentration ranges. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The human lysozyme was reported by Hancock to show a good synergy with the AMP protegrin against Enterococcus faecalis : indeed the MICs of protegrin and lysozyme were lowered from 16 and 6 μg/mL, when used alone, to 4 and 0.39 μg/mL, respectively, in combination [ 230 ]. The combination of human lysozyme with six different AMPs against P. aeruginosa was recently examined and the authors discovered that some AMPs manifest antagonistic interactions with hLys, in contrast to prior reports [ 231 ]. These results, according to the authors, must be considered for the future development of lysozyme and AMP combination therapies.…”
Section: Synergistic Activity Of Lysozymementioning
confidence: 96%
“…The human lysozyme was reported by Hancock to show a good synergy with the AMP protegrin against Enterococcus faecalis : indeed the MICs of protegrin and lysozyme were lowered from 16 and 6 μg/mL, when used alone, to 4 and 0.39 μg/mL, respectively, in combination [ 230 ]. The combination of human lysozyme with six different AMPs against P. aeruginosa was recently examined and the authors discovered that some AMPs manifest antagonistic interactions with hLys, in contrast to prior reports [ 231 ]. These results, according to the authors, must be considered for the future development of lysozyme and AMP combination therapies.…”
Section: Synergistic Activity Of Lysozymementioning
confidence: 96%
“…It catalyzes the breaking of β -1,4-glycosidic bonds of peptidoglycan in bacterial cell walls [ 1 , 2 ] and exerts broad-spectrum antibacterial activities against Gram-negative bacteria (GNB) and Gram-positive bacteria (GPB) in vitro [ 2 ]. LYS is present not only in human [ 3 ] but also in the egg whites of most avians [ 4 ]. Additionally, LYS also has many other biological properties, such as antimicrobial [ 2 ], anti-inflammatory [ 5 ], antitumor [ 6 , 7 ], and antiviral [ 1 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has recently been demonstrated that bacteria can develop resistance to AMPs and that their combined use allows to delay the evolution of pathogen resistance [ 8 , 9 ], the use of combined forms of lactoferrin-derived AMPs seems to be the most appropriate way to avoid the development of resistance. Such combinations can be based not only on AMPs or antibiotics [ 43 , 44 ], but also on enzymes that are active against different G(+) and G(−) bacteria [ 45 , 46 , 47 ]. In vitro studies of the combined use of various AMPs derived from human and bovine lactoferrin with traditional antibiotics revealed the presence of a synergistic effect between polypeptides and antibiotics; however, the obtained results were insufficient to produce therapeutic effects in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%